2022
DOI: 10.3390/ijerph19106125
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Preliminary Analysis of the Impact of Meteorological Conditions on the COVID-19 Epidemic

Abstract: Since the COVID-19 epidemic outbreak at the end of 2019, many studies regarding the impact of meteorological factors on the attack have been carried out, and inconsistent conclusions have been reached, indicating the issue’s complexity. To more accurately identify the effects and patterns of meteorological factors on the epidemic, we used a combination of logistic regression (LgR) and partial least squares regression (PLSR) modeling to investigate the possible effects of common meteorological factors, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Our study showed a negative correlation between WS and newly confirmed COVID-19 cases in Regions a, e, and f, aligning with earlier research [8,17,38,39,42,43] and supporting the hypothesis that higher wind speeds might dilute airborne virus particles, reducing transmission [44].…”
Section: Meteorological Factors and Covid-19 Incidencesupporting
confidence: 92%
“…Our study showed a negative correlation between WS and newly confirmed COVID-19 cases in Regions a, e, and f, aligning with earlier research [8,17,38,39,42,43] and supporting the hypothesis that higher wind speeds might dilute airborne virus particles, reducing transmission [44].…”
Section: Meteorological Factors and Covid-19 Incidencesupporting
confidence: 92%
“…Epidemics exhibit distinct transmission characteristics in varied spatial and temporal contexts. The spread of COVID-19, characterized by spatial heterogeneity, is significantly influenced by meteorological factors [34] . Changes in meteorological factors (temperature, humidity, wind, air pressure, and diffusion conditions, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…In late 2019, coronavirus disease 2019 (COVID- 19), the disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was first reported; subsequently, a pandemic ensued and was characterized by person-to-person transmission and asymptomatic patients (1,2). For at least half a year, COVID-19 rapidly spread worldwide over more than 200 countries and regions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the huge impacts that COVID-19 exerted on social economics and human lives worldwide, a large number of prevention and control measures have been employed in different countries (7,(13)(14)(15). Because the accurate simulation and prediction of infectious diseases can provide the scientific basis for adopting reasonable measurements, many COVID-19 models have been established to investigate disease variations and related impact factors and to predict future trends (16)(17)(18)(19). Among these models, ARIMA and SARIMA models have been widely applied to analyze the linear, nonlinear and seasonal characteristics of COVID-19 (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%